2020
DOI: 10.3390/jpm11010014
|View full text |Cite
|
Sign up to set email alerts
|

A Conformation Variant of p53 Combined with Machine Learning Identifies Alzheimer Disease in Preclinical and Prodromal Stages

Abstract: Early diagnosis of Alzheimer’s disease (AD) is a crucial starting point in disease management. Blood-based biomarkers could represent a considerable advantage in providing AD-risk information in primary care settings. Here, we report new data for a relatively unknown blood-based biomarker that holds promise for AD diagnosis. We evaluate a p53-misfolding conformation recognized by the antibody 2D3A8, also named Unfolded p53 (U-p532D3A8+), in 375 plasma samples derived from InveCe.Ab and PharmaCog/E-ADNI longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…The variation in the tannin content in pomelo peel and juice could be attributed to variety, environmental factors, and harvesting practices. More notably, the irrigation practices also affect the accumulation of tannin in the fruit [ 61 ]. However, the hydrolysable tannins showed a gradual increase, being lowest in immature fruit and highest in mature fruit.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in the tannin content in pomelo peel and juice could be attributed to variety, environmental factors, and harvesting practices. More notably, the irrigation practices also affect the accumulation of tannin in the fruit [ 61 ]. However, the hydrolysable tannins showed a gradual increase, being lowest in immature fruit and highest in mature fruit.…”
Section: Resultsmentioning
confidence: 99%
“…This study supports the effect of PTMs on p53 conformation and its role in AD. Recent studies (Piccirella et al, 2021;Abate et al, 2021) also showed the expression of a conformational variant of p53 in the plasma samples of asymptomatic and AD prodromal individuals confirming the role of the conformational variant of p53 in AD.…”
Section: Discussionmentioning
confidence: 75%
“…To further investigate the relationship of unfolded p53 isoforms in AD, Memo et al (2018) developed a monoclonal antibody (mAb) 2D3A8 to be highly specific for the p53 The recent study by Abate et al (2021) further evaluated the presence of the conformational variant of p53 using the mAb 2D3A8. Three hundred seventy-five plasma samples from two longitudinal AD studies were used in conjunction with a machine learning approach to create an algorithm to predict AD likelihood risk.…”
Section: The Conformational Variant Of P53 Detected In Admentioning
confidence: 99%
“…Assessment of U-p53 has now been improved by the development of a novel antibody (2D3A8) specifically targeting the AD clinically relevant U-p53 conformational variant (U-p53 AZ ) (Piccirella et al, 2021;Abate et al, 2020). To further improve its analytical performance, U-p53 AZ was quantified by the AlzoSure ® Predict method, a LC-ESI/MS/MS sequential technique using plasma samples from individuals at different stages of the AD continuum, available through the longitudinal AIBL cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, higher levels of U-p53 have been consistently detected in peripheral cells derived from patients with AD as compared with controls (Lanni et al, 2008;Lanni et al, 2010a;Stanga et al, 2012). Recently, a novel antibody (2D3A8) was developed to detect this AD-specific U-p53 variant (herein described as "U-p53 AZ ") (Abate et al, 2020), demonstrating its promising performance in predicting the AD risk at the preclinical and prodromal stages (Piccirella et al, 2021;Abate et al, 2020).…”
Section: Introductionmentioning
confidence: 99%